Filsafat Positivisme Hukum dalam Pemberantasan Pencucian Uang: Analisis Kepastian Hukum dan Implementasi di Indonesia - Rasji; Rupertus Arvinci Ngabut (CV Rewang Rencang, 2024)
Money laundering is a criminal act that has serious implications for a country's economic stability and financial system. In its eradication efforts, the positivism legal approach emphasizes the importance of legal certainty through strict regulations and rigid law enforcement in accordance with norms established by the competent authorities. Law No. 8 of 2010 serves as the primary legal foundation for preventing and combating money laundering. However, its implementation often faces challenges due to the rigidity of positivism, which fails to accommodate the evolving nature of financial crimes. Therefore, synergy between legal positivism and a more progressive approach is necessary to ensure the effectiveness of law enforcement against money laundering in Indonesia.